'The body is our masterpiece': learning to transform in Lima's tambores music. Issue 2 (4th May 2019) - Odria, Carlos
ABSTRACT: In this article I discuss the use of rehearsal drills among the tambores musicians of Villa El Salvador (VES), an underprivileged yet emerging district of Lima, Peru that was built and populated by Andean and mestizo settlers starting in the 1970s. Tambores is a drum genre derived from Afro-Brazilian batucada music that incorporates community-oriented values inherited from the seminal ideological principles established by the first wave of rural settlers. Starting in the early 2000s, grassroots organisations led by VES adolescents began developing and disseminating local pedagogies to promote tambores music as a conduit for galvanising communal engagement and solidarity. The article shows how VES musicians deploy rehearsal routines to fortify their grassroots initiatives, seeking to enfranchise other adolescents by incorporating bodily techniques for self-empowerment and dynamic socialisation. Through this pedagogical programme, tambores musicians employ the rehearsal as a space where the district's youth may fine-tune and 'transform' their bodies and social attitudes in order to become engaged and positively motivated members of the VES community.